Jane Goes North - A Novel - Lansdale, Joe R., 1951- (Burton, MI : Subterranean Press, 2020)
"Jane has lost her job at the laundry due to a ketchup package she forgot to remove from an expensive item, and her prospects look dim. To top off matters, her younger sister, who lives up north, and who Jane has problems with, is getting married and has mailed her an invitation that Jane believes was sent due to her sister not expecting her to be able to come. A long bout of sibling rivalry makes Jane all the more determined to go, even if her car has gone to hell. To make the journey, Jane forms an uncomfortable alliance with a grumpy, one-eyed, weight- lifting lady named Henry, who may or may not abandon her along the way, and has plans to see a doctor Henry claims can renew her sight"--Dust jacket flap.
Keywords: Sibling rivalry -- Fiction; Sisters -- Fiction; Automobile travel -- Fiction; Female friendship -- Fiction; Weight lifters -- Fiction; Road fiction; Picaresque fiction